Endovascular thrombectomy for acute ischaemic stroke with established large infarct: multicentre, open-label, randomised trial - Bendszus, Martin; Fiehler, Jens; Subtil, Fabien; Bonekamp, Susanne; Aamodt, Anne Hege; Fuentes, Blanca; Gizewski, Elke Ruth; Hill, Michael D.; Krajina, Antonin; Pierot, Laurent; Simonsen, Claus Z.; Zeleňák, Kamil; et al. (The lancet, 2023)
Background - Recent evidence suggests a beneficial effect of endovascular thrombectomy in acute ischaemic stroke with large infarct; however, previous trials have relied on multimodal brain imaging, whereas non-contrast CT is mostly used in clinical practice. - Methods - In a prospective multicentre, open-label, randomised trial, patients with acute ischaemic stroke due to large vessel occlusion in the anterior circulation and a large established infarct indicated by an Alberta Stroke Program Early Computed Tomographic Score (ASPECTS) of 3-5 were randomly assigned using a central, web-based system (using a 1:1 ratio) to receive either endovascular thrombectomy with medical treatment or medical treatment (ie, standard of care) alone up to 12 h from stroke onset. The study was conducted in 40 hospitals in Europe and one site in Canada. The primary outcome was functional outcome across the entire range of the modified Rankin Scale at 90 days, assessed by investigators masked to treatment assignment. The primary analysis was done in the intention-to-treat population. Safety endpoints included mortality and rates of symptomatic intracranial haemorrhage and were analysed in the safety population, which included all patients based on the treatment they received. This trial is registered with ClinicalTrials.gov, NCT03094715. - Findings - From July 17, 2018, to Feb 21, 2023, 253 patients were randomly assigned, with 125 patients assigned to endovascular thrombectomy and 128 to medical treatment alone. The trial was stopped early for efficacy after the first pre-planned interim analysis. At 90 days, endovascular thrombectomy was associated with a shift in the distribution of scores on the modified Rankin Scale towards better outcome (adjusted common OR 2·58 [95% CI 1·60-4·15]; p=0·0001) and with lower mortality (hazard ratio 0·67 [95% CI 0·46-0·98]; p=0·038). Symptomatic intracranial haemorrhage occurred in seven (6%) patients with thrombectomy and in six (5%) with medical treatment alone. - Interpretation - Endovascular thrombectomy was associated with improved functional outcome and lower mortality in patients with acute ischaemic stroke from large vessel occlusion with established large infarct in a setting using non-contrast CT as the predominant imaging modality for patient selection. - Funding - EU Horizon 2020.
Gesehen am 13.02.2024